TUTURAN PENGAJIAN GUS BAHA’ KITAB ARBAIN NAWAWI (KAJIAN SOSIOLINGUISTIK) - Ahmad Fajrul; Maskub Maskub; Khoirul Huda (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study was to describe the variety, value and function of Gus Baha's recitation of the Arbain Nawawi book on February 21, 2021 on the Bintang Songo YouTube channel 1926 PP. Izzati Nuril Qur'an Yogyakarta. The data collection technique used is the method of observation and documentation. The observation method is used to determine the form of speech contained in Gus Baha's recitation of the book of Arbain Nawawi. The documentation method is used to record the recitation of Gus Baha' recitation of the Arbain Nawawi book by focusing on variety, value and function. Based on the results of the study, it is known that the variety of speech in Gus Baha's recitation of the Arbain Nawawi book, namely the frozen variety, the official variety, the relaxed variety and the familiar variety. The value of speech in Gus Baha' recitation of the Arbain Nawawi book, the value of religious education, the value of honesty education, the value of tolerance education, the value of discipline education, the value of hard work education, the value of social care education and the value of responsibility education. The speech functions in Gus Baha' Arbain Nawawi recitation, namely congratulatory expressive speech functions, critical speech functions, complaining expressive speech functions, blame expressive speech functions, praise expressive speech functions and satire expressive speech functions.